Hepatobiliary Impairments in Patients with Inflammatory Bowel Diseases: The Current Approach - Vlad Alexandru Ionescu; Gina Gheorghe; Valentin Nicolae Varlas; Ana Maria Alexandra Stanescu; Camelia Cristina Diaconu (Gastroenterology Insights, 2022)
Inflammatory bowel disease (IBD) refers to chronic conditions with a low mortality but high disability. The multisystemic nature of these diseases can explain the appearance of some extraintestinal manifestations, including liver damage. Abnormal liver biochemical tests can be identified in approximately one third of patients with IBD and chronic liver disease in 5% of them. Among the liver diseases associated with IBD are primary sclerosing cholangitis, cholelithiasis, fatty liver disease, hepatic amyloidosis, granulomatous hepatitis, drug-induced liver injury, venous thromboembolism, primary biliary cholangitis, IgG4-related cholangiopathy, autoimmune hepatitis, liver abscesses or the reactivation of viral hepatitis. The most common disease is primary sclerosing cholangitis, a condition diagnosed especially in patients with ulcerative colitis. The progress registered in recent years in the therapeutic management of IBD has not eliminated the risk of drug-induced liver disease. Additionally, the immunosuppression encountered in these patients increases the risk of opportunistic infections, including the reactivation of viral hepatitis. Currently, one of the concerns consists of establishing an efficiency and safety profile of the use of direct-acting antiviral agents (DAA) among patients with hepatitis C and IBD. Early diagnosis and optimal treatment of liver complications can improve the prognoses of these patients.